2012
DOI: 10.1097/mot.0b013e3283592622
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination in solid-organ transplant recipients

Abstract: The administration of influenza vaccination is strongly recommended in SOT recipients and their relatives. Further research is needed for improving the immunogenicity of influenza vaccine in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…The protection reported following trivalent inactivated influenza vaccination (29, 30) has not always been observed after vaccination against other viral illnesses (31, 32), perhaps because in contrast to influenza, people lack preexisting memory responses to these other viruses. Even with influenza vaccination, the response in transplanted patients is often blunted (33, 34). …”
Section: Infections and Alloimmunitymentioning
confidence: 99%
“…The protection reported following trivalent inactivated influenza vaccination (29, 30) has not always been observed after vaccination against other viral illnesses (31, 32), perhaps because in contrast to influenza, people lack preexisting memory responses to these other viruses. Even with influenza vaccination, the response in transplanted patients is often blunted (33, 34). …”
Section: Infections and Alloimmunitymentioning
confidence: 99%
“…In addition, conflicting data exist on immune responses to influenza vaccine in this population. Some studies demonstrate lower antibody responses in SOT recipients when compared to age‐matched healthy controls, while another study revealed similar antibody titers, but decreased interferon gamma production in SOT recipients when compared to controls . Recently, a HD trivalent inactive influenza vaccine (Fluzone HD) with four times the standard antigenic dose was approved for use in individuals ≥65 yr of age.…”
mentioning
confidence: 99%
“…Influenza is associated with significant morbidity in solidorgan transplant (SOT) recipients [1,2]. While the main preventive strategy against influenza after transplantation remains annual influenza vaccination [3], the immunogenicity and efficacy of influenza vaccine are suboptimal in this population [4].…”
Section: Introductionmentioning
confidence: 99%